2018
DOI: 10.1590/1414-431x20187574
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-221 promotes cell proliferation, migration, and differentiation by regulation of ZFPM2 in osteoblasts

Abstract: Bone fracture is a common medical condition, which may occur due to traumatic injury or disease-related conditions. Evidence suggests that microRNAs (miRNAs) can regulate osteoblast differentiation and function. In this study, we explored the effects and mechanism of miR-221 on the growth and migration of osteoblasts using MC3T3-E1 cells. The expression levels of miR-221 in the different groups were measured by qRT-PCR. Then, miR-221 mimic and inhibitor were transfected into MC3T3-E1 cells, and cell viability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 37 publications
3
34
0
Order By: Relevance
“…miRNAs are generally regarded as post-transcriptional regulators that check the process of proliferation, apoptosis, differentiation and development [64]. Several miRNAs are documented to regulate the process of osteogenic proliferation, such as excessive expression of miR-221 and miR-215 in the mouse osteoblast cells encourages the proliferative capacity of the cells [65,66]. Likewise, downregulation of miR-185 results in the declined osteoblast proliferation [67].…”
Section: Mirna Regulation In Osteoblast Proliferationmentioning
confidence: 99%
“…miRNAs are generally regarded as post-transcriptional regulators that check the process of proliferation, apoptosis, differentiation and development [64]. Several miRNAs are documented to regulate the process of osteogenic proliferation, such as excessive expression of miR-221 and miR-215 in the mouse osteoblast cells encourages the proliferative capacity of the cells [65,66]. Likewise, downregulation of miR-185 results in the declined osteoblast proliferation [67].…”
Section: Mirna Regulation In Osteoblast Proliferationmentioning
confidence: 99%
“…Studies on miRNAs have demonstrated that the regulation of the target genes affects the expression of regulators upstream and downstream of each signaling pathway, to regulate the osteogenic differentiation process [54]. Runx2 is a transcription factor that plays an important role in osteoblast differentiation [55], which is precisely or indirectly regulated by many miRNAs, including miR-221 [56,57], miR-133a-5p [58], miR-467g [59], miR-218 [60,61], and miR-210 [62]. The expression of Osx can be downregulated by some miR-NAs, inhibiting osteogenic differentiation, such as miR-145 [63] and miR-143 [64,65].…”
Section: Osteoblast Exosomesmentioning
confidence: 99%
“…Moreover, a certain amount of IGF-1R was detected in MC3T3-E1 cells (Joung et al, 2013). The cells were cultured in Dulbecco's minimal essential medium (DMEM) (Hyclone, United States) supplemented with 10% heat-inactivated fetal bovine serum and 1% streptomycin/penicillin (Gibco, United States) in an incubator with 5% CO 2 at 37 • C. At 80% cell confluence, the culture medium was changed to a differentiation medium that contained 50 mg/mL ascorbic acid (Sigma, United States) and 10 mmol/L β-glycerophosphate (Sigma, United States) (Zheng et al, 2018).…”
Section: Cell Culturementioning
confidence: 99%